The experience of Greek-Cypriot individuals living with mental illness: Preliminary results of a phenomenological study - Kaite, Charis P.; Karanikola, Maria; Vouzavali, Foteini; Koutroubas, Anna; Merkouris, Anastasios; Papathanassoglou, Elizabeth (My University, 2016)
Background: Research evidence shows that healthcare professionals do not fully comprehend the difficulty involved in problems faced by people living with severe mental illness (SMI). As a result, mental health service consumers do not show confidence in the healthcare system and healthcare professionals, a problem related to the phenomenon of adherence to therapy. Moreover, the issue of unmet needs in treating individuals living with SMI is relared to their quality of life in a negative way. Methods: A qualitative methodological approach based on the methodology of van Manen phenomenology was employed through a purposive sampling of ten people living with SMI. The aim was to explore their perceptions and interpretations regarding: a) their illness, b) their self-image throughout the illness, c) the social implications following their illness, and d) the quality of the therapeutic relationship with mental health nurses. Participants were recruited from a community mental health service in a Greek-Cypriot urban city. Data were collected through personal, semi-structured interviews. Results: Several main themes were identified through the narratives of all ten participants. Main themes included: a) The meaning of mental illness, b) The different phases of the illness in time, c) The perception of the self during the illness, d) Perceptions about the effectiveness of pharmacotherapy, e) Social and personal consequences for participants following the diagnosis of mental illness, f) Participants' perceptions regarding mental health professionals and services and g) The therapeutic effect of the research interview on the participants. Conclusions: The present study provides data for the enhancement of the empathic understanding of healthcare professionals regarding the concerns and particular needs of individuals living with SMI, as well as the formation of targeted psychosocial interventions based on these needs. Overall, the present data illuminate the necessity for the reconstruction of the provided mental healthcare in Cyprus into a more recovery- oriented approach in order to address personal identity and self-determination issues and the way these are related to management of pharmacotherapy. Qualitative studies aiming to further explore issues of self-identity during ill health and its association with adherence to therapy, resilience and self-determination, are also proposed.
Keywords: Bipolar disorder; Depression; Mental health nurses; Phenomenology; Psychosis; Van Manen